Effects of salinity, temperature and ph on harmful algal blooms species in kota kinabalu coastal waters - Aimimuliani Adam (2010)
The occurrence of harmful algal blooms (HAS) since last three decades in Sabah waters had caused poisoning incidents, which lead to the human and organism illness. Some HASs species also caused damages especially lost in the local aquaculture industries. Realizing the lack of information available regarding to the factors affecting the bloom, thus this study was carried out. The objective of this study was to determine the effects of physico-chemical properties of seawater (Le. salinity, temperature and pH) on the HASs species viz. Pyrodinium bahamense var. compressum, Cochlodinium polykrikoides and Gymnodinium catenatum in the Kota Kinabalu waters from January to December 2007. At six sampling stations, physical properties of seawater were measured in-situ at sea surface using multi probes (Hydrolab Surveyor 4 and HANNA Instrument) and phytoplankton samples were collected at 0.5 meter depth using water sampler. The highest peak of C polykrikoides was recorded on 3rd December 2007 (1.54 x 107 cells L-1 ). During the bloom, sea surface salinity, temperature and pH recorded were 26.4 psu, 29 O( and 8.78, respectively. Maximum concentration of G. catenatum was also reported in December with cell densities of 1.24 x 106 cells L-1 • Pyrodinium bahamense var. compressum reached a maximum concentration on August, with the cell density of 2 x 104 cells L-1 • During the bloom, salinity, temperature and pH were 30.9 psu, 31.3 O( and 8.50, respectively. Salinity and pH of seawater were positively correlated (p<0.05) to the cell concentrations of C polyknkoides, whereas temperature showed negative correlation (p<0.05). No correlation was observed between the physico-chemical parameters with cell density of G. catenatum. However, negative correlation was observed between salinity and cell density of P. bahamense var. compressum (p<0.05), whereas temperature showed positive correlation. This study is useful in order to understand the mechanism of HASs occurrence and this may help government or any relevant agencies in mitigate and manage HAS problems in Sabah.